Continuous Threshold Harvesting Intermediate Predator in Food Chain Model - S. A. Wuhaib (Tikrit Journal of Pure Science, 2023)
This paper presents a three-species food chain system, which consists of intermediate predator population that depends only on prey population, and top predator population that depends only on intermediate predator population. We study this model when the intermediate predator exposed to the risk of harvest.